Teacher Autonomy: A Critical Review of the Research and Concept beyond Applied Linguistics - Usma Wilches, Jaime (Íkala, Revista de Lenguaje y Cultura, 2007)
In this paper I will review conceptual and empirical research on teacher autonomy beyond the limits of applied linguistics. Research shows that teacher autonomy can be conceptualized as a personal sense of freedom from interference or in terms of teachers’ exercise of control over school matters. This review clarifi es the meaning of teacher autonomy, provides valuable insights about different domains in which teachers exercise their control, and explores some of the personal and contextual factors that affect their performance. This paper confi rms the necessity to analyze teacher autonomy beyond a particular field Received: 27-03-07 / Accepted: 18-07-07 How to reference this article: Usma Wilches, J. (2007). Teacher Autonomy: A Critical Review of the Research and Concept beyond Applied Linguistics. Íkala. 12(1), pp. 245 – 275.